MOTIVASI PETANI GARAM DALAM MELAKUKAN USAHATANI GARAM DI DESA PINGGIR PAPAS KECAMATAN KALIANGET KABUPATEN SUMENEP - Hasan, Fuad; Rizal, Moh.; Sunyigono, Andrie K. (Universitas Sebelas Maret, 2023)
There are several risks that must be faced by salt farmers in salt farming, such as price instability, uncertain weather/climate, and competition for imported salt, however there are still many salt farmers who do salt farming, which means there is still motivation to do so. The purpose of this study was to determine the level of motivation and factors related to the motivation of salt farmers in doing salt farming. A sample of 42 salt farmers in Pinggir Papas Village, Kalianget District, was taken by purposive sampling. Data collected by structured interviews. Data analysis was done by quantitative descriptive and Spearman Rank correlation test. The result of this research is that the motivation level of salt farmers in Pinggir Papas Village, Kalianget District, Sumenep Regency was in high category. Factors that are positively related to the motivation of farmers (pegaram) were social aspects and economic aspects where the social aspect has a higher close relationship than the economic aspect. While the government aspect has a negative correlation coefficient